Pediatric Heart Failure, Lagging, and Sagging of Care in Low Income Settings: A Hospital Based Review of Cases in Ethiopia - Solmon Gebremariam; Tamirat Moges (Cardiology Research and Practice)
Introduction. Causes of acute heart failure in children range from simple myocarditis complicating chest infection to complex structural heart diseases. Objective. To describe patterns, predictors of mortality, and management outcomes of acute heart failure in children. Methods. In retrospective review, between February 2012 and October 2015 at a tertiary center, 106 admitted cases were selected consecutively from discharge records. Data were extracted from patients chart and analyzed using SPSS software package. t-test and statistical significance at P value < 0.05 with 95% CI were used. Result. Acute heart failure accounted for 2.9% of the total pediatric admissions. The age ranged from 2 months up to 14 years with mean age of 8 years. Male to female ratio is 1 : 2.1. Rheumatic heart disease accounted for 53.7%; pneumonia, anemia, infective endocarditis, and recurrence of acute rheumatic fever were the main precipitating causes. Death occurred in 19% of cases. Younger age at presentation, low hemoglobin concentration, and undernutrition were associated with death with P value of 0.00, 0.01, and 0.02, respectively. Conclusions and Recommendation. Pediatric heart failure in our settings is diagnosed mainly in older age groups and mostly precipitated due to preventable causes. Significant mortality is observed in relation to factors that can be preventable in children with underlying structural heart disease. Early suspicion and diagnosis of cases may reduce the observed high mortality.